Ultrasonic characterization of edible oils using a generalized fractional model. (February 2018) - Alouache, B.; Laux, D.; Hamitouche, A.; Bachari, K.; Boutkedjirt, T.
Highlights: Use of the fractional model in ultrasonic oils characterization. Ultrasonic measurements of the attenuation coefficient of olive and soya oils in the MHz frequency range. Application of the model on the ultrasonic data to derive the viscoelastic parameters of the two oils. Abstract: The attenuation coefficient of ultrasonic waves propagating in different materials, particularly oils, is governed by a frequency-dependent power law with an exponent ranging between 1 and 2. Classical models such as the thermo-viscous one can't often allow describing the viscoelastic behavior of these materials. To describe olive and soybean oils behavior, a fractional model was chosen. This model is based on a constitutive stress-strain equation with a fractional derivative of time. Within the limit of the low frequency approximation, this model helps to deduce the material's viscoelastic parameters. Ultrasonic measurements were carried out, on olive oil and soybean oil samples, over a frequency range extending from 4 to 16 MHz. The obtained results, for the ultrasonic phase velocity, viscosity coefficient and relaxation time, shows the efficiency of using this model in determining the oils viscoelastic properties and to distinguish the two types of oils.